Perancangan Prototipe Sistem Manajemen Pengetahuan Antar Universitas (Studi Kasus IPB Dan UNPAK) - Ibrahim, Firmansyah; Hermadi, Irman; Buono, Agus (Perpustakaan IPB, 2015)
The rapid development of knowledge encourages universities to collaborate on their knowledge in specific expertise field to create an equitable distribution of knowledge. Program of computer science at Bogor Agriculture University (IPB) is a superior expertise in the field of agriculture while Pakuan University (UNPAK) is superior expertise in the field of electronics. The aim of this study was to design a prototype of knowledge management system as the knowledge sharing for learning of inter-universities using Knowledge Management System Life Cycle (KMSLC) method. The study result was Joomla one kind of Content Management System (CMS) can be used to share knowledge in the form of discussion forums and combining various info from IPB and UNPAK in one interface including news, announcements, agenda, and social media. This CMS also collaborate with applications Electronic Learning System (ELS) Moodle and Hyper Text Markup Language (HTML). ELS Moodle serves as an application in learning of inter-university with the single sign concept which was run in a single interface, while HTML serves as a search engine knowledge by generating external link that combines 2 KMS from IPB and UNPAK into one interface. The conclusion was the knowledge sharing for learning of inter-university can be done with the design of knowledge management system through collaboration three different systems.Keywords: CMS Joomla, ELS Moodle, HTML search engine, KMSLC, Knowledge Management Systems, Prototype